Etique and publicity OnLine - Araceli CASTELLÓ MARTÍNEZ (Fonseca: Journal of Communication, 2015)
Internet consolidation as an advertising medium requires a review of the legal and ethical principles applicable to advertising initiatives in the digital world, also taking into account the peculiarities of new digital platforms, such as the Social Media